MicroRNAs, Major Players in B Cells Homeostasis and Function - Danger, Richard; Braza, Faouzi; Giral, Magali; Soulillou, Jean-Paul; Brouard, Sophie (Frontiers in Immunology, 2014)
As a main actor in humoral immunity, B cells participate in various antibody-related disorders. However, a deeper understanding of B-cell differentiation and function is needed in order to decipher their immune-modulatory roles, notably with the recent highlighting of regulatory B cells. microRNAs (miRNAs), key factors in various biological and pathological processes, have been shown to be essential for B cell homeostasis, and therefore understanding their participation in B cell biology could help identify biomarkers and contribute towards curing B-cell related immune disorders. This review aims to report studies casting light on the roles played by microRNAs in B-cell lineage and function and B cell-related immune pathologies.